Novel agents in antiplatelet therapy - (:unkn) unknown (My University, 2010)
Antiplatelet therapy is the cornerstone of management of acute coronary syndromes. Currently used antiplatelet drugs present several limitations that provoke new searches. These limitations include resistance, delay in the onset of action, risk for bleeding, variations in the individual response, and interaction with other medications (i.e. proton pump inhibitors, calcium channel blockers). New concepts and medications have emerged for the effective inhibition of platelets. Prasugrel, AZD6140 (ticagrelor), cangrelor, and SCH 530348 (thrombin receptor antagonist) are among some of the novel agents that survived randomized trials. In this review, we aimed to summarize novel concepts and agents in antiplatelet therapy.
Keywords: Humans; Aspirin; Platelet Aggregation Inhibitors; Adenosine; Thiophenes; Acute Coronary Syndrome; Prasugrel Hydrochloride; Purinergic P2Y Receptor Antagonists; Piperazines; Lactones; Adenosine Monophosphate; Clopidogrel; Pyridines; Receptors, Thrombin; Ticagrelor; Ticlopidine